Post-anticoagulant D-dimer is a highly prognostic biomarker of COVID-19 mortality. Issue 3 (5th July 2021) - Song, Xiaoyu; Ji, Jiayi; Reva, Boris; Joshi, Himanshu; Calinawan, Anna Pamela; Mazumdar, Madhu; Wisnivesky, Juan P.; Taioli, Emanuela; Wang, Pei; Veluswamy, Rajwanth R.
Clinical biomarkers that accurately predict mortality are needed for the effective management of patients with severe coronavirus disease 2019 (COVID-19) illness. In this study, we determine whether changes in D-dimer levels after anticoagulation are independently predictive of in-hospital mortality. Adult patients hospitalised for severe COVID-19 who received therapeutic anticoagulation for thromboprophylaxis were identified from a large COVID-19 database of the Mount Sinai Health System in New York City (NY, USA). We studied the ability of post-anticoagulant D-dimer levels to predict in-hospital mortality, while taking into consideration 65 other clinically important covariates including patient demographics, comorbidities, vital signs and several laboratory tests. 1835 adult patients with PCR-confirmed COVID-19 who received therapeutic anticoagulation during hospitalisation were included. Overall, 26% of patients died in the hospital. Significantly different in-hospital mortality rates were observed in patient groups based on mean D-dimer levels and trend following anticoagulation: 49% for the high mean-increase trend group; 27% for the high-decrease group; 21% for the low-increase group; and 9% for the low-decrease group (p<0.001). Using penalised logistic regression models to simultaneously analyse 67 clinical variables, the high increase (adjusted odds ratios (ORadj ): 6.58, 95% CI 3.81–11.16), low increase (ORadj : 4.06, 95% CI 2.23–7.38) and high decrease (ORadj : 2.37; 95% CI 1.37–4.09) D-dimer groups (reference: low decrease group) had the highest odds for in-hospital mortality among all clinical features. Changes in D-dimer levels and trend following anticoagulation are highly predictive of in-hospital mortality and may help guide resource allocation and future studies of emerging treatments for severe COVID-19. In a retrospective study of 1835 severely ill #COVID19 patients on therapeutic anticoagulation for thromboprophylaxis during hospitalisation, post-anticoagulant D-dimer levels and trends were highly significant and independent predictors of mortality https://bit.ly/3qw4Aah